Respuesta :

cher
Equation 1)  y = 3x + 1
Equation 2)  4y = 12x + 4

For BOTH equations, we must have x and y on the same side, so simply move the x's to the other side.

For equation 1, subtract 3x from both sides.

1)  -3x + y = 1

For equation 2, subtract 12x from both sides.

2)  -12x + 4y = 4

Now, multiply ALL of equation 1 by 4 so that both equations have (4y) in them.

1)  4(-3x + y = 1)

Simplify.

1)  -12x + 4y = 4

2)  -12x + 4y = 4

Subtract equations from one another.

0 = 0

Therefore, there are infinite solutions.

~Hope I helped!~